O Tai Chi Chuan reduz o estresse, mas não a ansiedade de estudante do ensino fundamental - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The number of people with stress and anxiety has been growing constant and consistently. These illnesses are also present in schools, causing learning problems in the students. These diseases are characterized by the loss of homeostasis, which causes a alert into the body to the danger. As this imbalance becomes chronic, the amygdala and the HPA axis are overstimulated. This situation maintains the constant release of hormones like adrenaline and cortisol. The cortisol inhibits the hippocampus, impairing the processes of memorization and learning. In view of this it is important to study non-drug alternatives of stress and anxiety control. Such as contemplative practices, for example Tai Chi Chuan. Tai Chi Chuan is an ancient Chinese therapeutic martial art that has been studied as an assistance in reducing stress and anxiety. Therefore, our goal was to study the effects of Tai Chi Chuan in elementary school children. To achieve this goal, we implemented a methodology that consisted in recruiting volunteers from 2 classes from the 9th grade of elementary school, composing a group of 34 students (16 male and 18 female, with an average of 14 years). Randomly, a class was chosen to be the test. They practiced Zhanzhuang, a basic Tai Chi Chuan exercise, and the other group, the control, performed stretching exercises. The exercises were offered 3 times a week, with sessions of 20 minutes, during the same class shift. Twenty sessions were performed during August to October 2017. The IDATE Trace and State tests were used to evaluate the anxiety levels, and the ESI - Stress Test for Childhood Stress was applied to measure the stress levels. These tests were made in two moments; pre-intervention and post-intervention. The results suggest that the practice of Tai Chi Chuan decreased stress in the test group, but didn’t reduce anxiety in this group. After the application of the post-intervention tests, a questionnaire was also applied to evaluate students' perceptions about the exercises and the perception of the classes was very positive, stating that these interventions would help them to improve their performance in the classroom and also during the evaluations. We conclude these techniques, besides being necessary, are effective in the school context for the management of stress and the children’s improvement in school.
Tai Chi Chuan reduces stress, but not anxiety for elementary school students
Keywords: Educação e neurociência; Education and neuroscience; Anxiety; School; Estresse; Ansiedade; Aprendizagem; Tai Chi Chuan; Escola; Learning; Stress; CNPQ::CIENCIAS DA SAUDE